Isolation and Characterization of Canthaxanthin Biosynthesis Genes from the Photosynthetic Bacterium Bradyrhizobium sp. Strain ORS278 - Hannibal, Laure (American Society for Microbiology, 2000)
A carotenoid biosynthesis gene cluster involved in canthaxanthin production was isolated from the photosynthetic Bradyrhizobium sp. strain ORS278. This cluster includes five genes identified as crtE, crtY, crtI, crtB, and crtW that are organized in at least two operons. The functional assignment of each open reading frame was confirmed by complementation studies.